2021
DOI: 10.1111/joor.13153
|View full text |Cite
|
Sign up to set email alerts
|

Construction of virtual intercuspal occlusion: Considering tooth displacement

Abstract: Common impressions cannot accurately duplicate the dental occlusion under occlusal force due to tooth displacement and mandibular deformation. To establish new methods to construct virtual intercuspal occlusion and assess their construction accuracy. The intraoral occlusal contacts of posterior teeth of 15 subjects were recorded with 8 μm and 100 μm articulating paper, respectively, and the marked teeth and buccal bite data were scanned with an intraoral scanner. The virtual dental occlusions were separately d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…in the same mechanical articulator with the working casts mounted with the interocclusal record randomly‐allocated as above. Considering the physiologic mobility of natural teeth when occluding (Li et al, 2021; Miura et al, 1998), the implant prostheses' occlusal clearance in working casts was designed to achieve light contact by extracting a 38‐μm articulating paper (SHOFU) with light resistance in MIP. The implant prostheses' occlusal contacts in both MIP and eccentric position were detected using a 100‐μm articulating paper (BK‐51 Blue and BK‐52 Red; Dr. Jean Bausch GmbH) in working casts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…in the same mechanical articulator with the working casts mounted with the interocclusal record randomly‐allocated as above. Considering the physiologic mobility of natural teeth when occluding (Li et al, 2021; Miura et al, 1998), the implant prostheses' occlusal clearance in working casts was designed to achieve light contact by extracting a 38‐μm articulating paper (SHOFU) with light resistance in MIP. The implant prostheses' occlusal contacts in both MIP and eccentric position were detected using a 100‐μm articulating paper (BK‐51 Blue and BK‐52 Red; Dr. Jean Bausch GmbH) in working casts.…”
Section: Methodsmentioning
confidence: 99%
“…in the same mechanical articulator with the working casts mounted with the interocclusal record randomlyallocated as above. Considering the physiologic mobility of natural teeth when occluding (Li et al, 2021;Miura et al, 1998) Subsequently, the crown's axial surface was colored and glazed.…”
Section: Clinical Evaluation Of the Implant Prosthesesmentioning
confidence: 99%
“…3. Functional occlusal morphology –the maxillary and mandibular teeth models will be mounted to a virtual articulator (exocad; DentalCAD, exocad) at average setting and the whole system is instructed to perform simulated jaw movements to determine if there is any occlusal interference [ 9 , 37 ].…”
Section: Study Protocolmentioning
confidence: 99%
“…The results showed that the virtual dental occlusion constructed using the STR method demonstrated a better location, count, and area of intraoral occlusal contacts than that of the BBR method. But the occlusal contacts recorded with 100 µm articulating paper were set as the reference in the previous study 20 . All points less than 100 µm of the occlusal surfaces between casts can be calculated.…”
mentioning
confidence: 99%
“…[16][17][18][19] Prostheses made using these digital casts exhibit no contact or have light occlusal contacts, resulting in lower masticatory efficiency. 15,17 Considering tooth displacement under bite force, a segmented tooth registration (STR) method was established 20 to construct virtual dental occlusion. The digital dentitions were segmented into single teeth, and the single teeth were aligned to buccal bite data respectively, to conform to the displacement of teeth under bite force.…”
mentioning
confidence: 99%